The effects of boma design on stress-related behaviour in juvenile translocated African elephants - Marion Garaï (Pachyderm)
Reviews experience of confining translocated juveniles in bomas or pens of different types. Confinement with restricted food and view of the outside area tends to bring out aggressive behaviour. Open paddocks with electric fences are recommended over closed wooden paddocks.